Surveillance imaging with FDG-PET/CT in the post-operative follow-up of stage 3 melanoma. (12th April 2018) - Lewin, J; Sayers, L; Kee, D; Walpole, I; Sanelli, A; te Marvelde, L; Herschtal, A; Spillane, J; Gyorki, D; Speakman, D; Estall, V; Donahoe, S; et al.
Abstract: Background: As early detection of recurrent melanoma maximizes treatment options, patients usually undergo post-operative imaging surveillance, increasingly with FDG-PET/CT (PET). To assess this, we evaluated stage 3 melanoma patients who underwent prospectively applied and sub-stage-specific schedules of PET surveillance. Patients and methods: From 2009, patients with stage 3 melanoma routinely underwent PET +/− MRI brain scans via defined schedules based on sub-stage-specific relapse probabilities. Data were collected regarding patient characteristics and outcomes. Contingency analyses were carried out of imaging outcomes. Results: One hundred and seventy patients (stage 3A: 34; 3B: 93; 3C: 43) underwent radiological surveillance. Relapses were identified in 65 (38%) patients, of which 45 (69%) were asymptomatic. False-positive imaging findings occurred in 7%, and 6% had treatable second (non-melanoma) malignancies. Positive predictive values (PPV) of individual scans were 56%−83%. Negative scans had predictive values of 89%−96% for true non-recurrence [negative predictive values (NPV)] until the next scan. A negative PET at 18 months had NPVs of 80%−84% for true non-recurrence at any time in the 47-month (median) follow-up period. Sensitivity and specificity of the overall approach of sub-stage-specific PET surveillance were 70% and 87%, respectively. Of relapsed patients, 33 (52%) underwent potentially curative resection and 10 (16%) remained disease-free after 24 months (median). Conclusions: Application of sub-stage-specific PET in stage 3 melanoma enables asymptomatic detection of most recurrences, has high NPVs that may provide patient reassurance, and is associated with a high rate of detection of resectable and potentially curable disease at relapse.